Hyperglycemia exerts disruptive effects on the secretion of TGF-β1 and its matrix ligands, decorin and biglycan, by mesenchymal sub-populations and macrophages during bone repair - Yusop, Norhayati; Moseley, Ryan; Waddington, Rachel J. (Frontiers in Dental Medicine, 2023)
Introduction Bone has a high capacity for repair, but for patients with uncontrolled type 2 diabetes mellitus (T2DM), the associated hyperglycemia can significantly delay osteogenic processes. These patients respond poorly to fracture repair and bone grafts, leading to lengthy care plans due to arising complications. Mesenchymal stromal cells (MSCs) and M2 macrophages are both major sources of transforming growth factor-β1 (TGF-β1), a recognized mediator for osteogenesis and whose bioavailability and activities are further regulated by matrix small leucine-rich proteoglycans (SLRPs), decorin and biglycan. The aim of this study was to investigate how in vivo and in vitro hyperglycemic (HGly) environments can influence the levels of TGF-β1, decorin, and biglycan during bone repair, with additional consideration for how long-term glucose exposure and cell aging can also influence this process. Results Following bone healing within a T2DM in vivo model, histological and immunolabeling analyses of bone tissue sections confirmed delayed healing, which was associated with significantly elevated TGF-β1 levels within the bone matrices of young diabetic rats, compared with their normoglycemic (Norm) and aged counterparts. Studies continued to assess in vitro the effects of normal (5.5 mM) and high (25 mM) glucose exposure on the osteogenic differentiation of compact bone-derived mesenchymal stromal cells (CB-MSCs) at population doubling (PD)15, characterized to contain populations of lineage-committed osteoblasts, and at PD150, where transit-amplifying cells predominate. Short-term glucose exposure increased TGF-β1 and decorin secretion by committed osteoblasts but had a lesser effect on transit-amplifying cells. In contrast, the long-term exposure of CB-MSCs to high glucose was associated with decreased TGF-β1 and increased decorin secretion. Similar assessments on macrophage populations indicated high glucose inhibited TGF-β1 secretion, preventing M2 formation. Discussion Collectively, these findings highlight how hyperglycemia associated with T2DM can perturb TGF-β1 and decorin secretion by MSCs and macrophages, thereby potentially influencing TGF-β1 bioavailability and signaling during bone repair.